The evaluation of the correctional program which was applied to the Ukrainian adolescents - Ukhanova, A. (Journal of Education, Health and Sport, 2016)
The effectiveness of the correctional program which was applied to the Ukrainian adolescents has been analyzed. There were 184 adolescents under observation: 92 (50%) males and 92 (50%) females. 70.1% of the respondents aged 14 y.o., 8.2% of the persons under observation aged 13 y.o., 21.1% - 15 y. o. and 0.5% were of 16 y.o. Consecutive measurements were made before the correctional program and after it. Beck Depression Inventory; state of health in the last two weeks; actual well-being; suicidal thoughts and desires; lack of meaning in life; suicidal fantasies; suicidal plans; anxiety; guilty feeling; feeling of punishment were analyzed. Besides several variables such as "My future seems to me gloomy", "How often did most students feel good and helpful?", "I try to treat others well, I care about their feelings", "I try to help, if somebody is sick, upset or offended", "Basically, I am well treated by my peers", "I often and willingly help others " also were studied. After the correctional program use the male adolescents had the decreased level of depression, anxiety and punishment, they less often fantasized about death and less often had suicidal thoughts. Adolescents’ altruistic inclinations also decreased, such as reluctance to help, if someone is sick, upset or offended. In the group of female adolescents the feeling of punishment decreased and the desire to treat about others, to care about their feelings grew.